1989
DOI: 10.1021/la00090a007
|View full text |Cite
|
Sign up to set email alerts
|

A method using total internal reflection microscopy and radiation pressure to study weak interaction forces of particles near surfaces

Abstract: An apparatus has been built which allows, by radiation pressure forces, the manipulation of a single colloid particle, immersed in water, close to a flat surface. The particle movement is monitored by total internal reflection microscopy (TIRM). Preliminary results are presented which illustrate the usefulness of the technique for studying the weak interactions between a 10-µ polystyrene latex particle and a quartz glass surface. An interaction potential energy curve as a function of the relative separation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…This tech- nique was first demonstrated by Brown et al (15) and was upward force on the particle, which acts to effectively lower the net particle weight, can be measured and subtracted from later adopted in a similar design by Walz and Prieve (16). It was shown that a laser beam directed upward against the measured potential energy profiles so that it does not affect the final results.…”
Section: Methodsmentioning
confidence: 99%
“…This tech- nique was first demonstrated by Brown et al (15) and was upward force on the particle, which acts to effectively lower the net particle weight, can be measured and subtracted from later adopted in a similar design by Walz and Prieve (16). It was shown that a laser beam directed upward against the measured potential energy profiles so that it does not affect the final results.…”
Section: Methodsmentioning
confidence: 99%
“…2. The idea of using light forces to control the movement of the particle has been introduced to the TIRM method by Brown et al 28 and Walz et al 29 In our case both tweezers were formed by a 200 mW frequency doubled Nd:YAG laser (ϭ532 nm). As the upper tweezer we employed a strongly focused laser beam with an adjustable intensity of 50-150 mW.…”
Section: The Experimentsmentioning
confidence: 99%
“…Adamczyk et al [3] experimentally confirmed Brenner's correction factor to the bulk particle mobility by measuring the sedimentation rate of nylon spheres through a viscous oil toward different shaped surfaces. Brown and Staples [4][5][6] studied the dynamics of Brownian particles above a quartz plate at small separation distance using the combined optical techniques of radiation pressure and total internal reflection microscopy (TIRM). The authors calculated the absolute separation distance of the particle from the surface assuming Brenner's lubrication theory to be valid.…”
Section: Introductionmentioning
confidence: 99%